2017
DOI: 10.1002/mnfr.201700134
|View full text |Cite
|
Sign up to set email alerts
|

High salt diet impairs memory‐related synaptic plasticity via increased oxidative stress and suppressed synaptic protein expression

Abstract: ScopeA high salt (HS) diet is detrimental to cognitive function, in addition to having a role in cardiovascular disorders. However, the method by which an HS diet impairs cognitive functions such as learning and memory remains open.Methods and resultsIn this study, we found that mice on a 7 week HS diet demonstrated disturbed short‐term memory in an object‐place recognition task, and both 4 week and 7 week HS treatments impaired long‐term memory, as evidenced in a fear conditioning test. Mechanistically, the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 58 publications
7
55
2
Order By: Relevance
“…The results of the behavioral experiment indicated that intraventricular injection of A β 1–42 caused severe learning and memory impairments. Numerous studies have established that decreased hippocampal synaptic plasticity was one of the key elements in cognitive impairment . Thus, we investigated the expression of proteins related to synaptic plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the behavioral experiment indicated that intraventricular injection of A β 1–42 caused severe learning and memory impairments. Numerous studies have established that decreased hippocampal synaptic plasticity was one of the key elements in cognitive impairment . Thus, we investigated the expression of proteins related to synaptic plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…Another study found poorer place recognition memory and long-term contextual fear memory in mice fed a high-salt diet (8% NaCl vs 0.4% control diet) for 7 weeks. 27 These cognitive impairments were accompanied by increased oxidative stress and downregulation of synaptic protein and plasticity markers in the hippocampus. A comparable study in rats found that nine weeks' consumption of a high-salt diet (8% NaCl vs 0.26% control diet) impaired spatial memory in the Morris Water Maze and in a contextual fear conditioning paradigm.…”
Section: Cognitive Effects Of Dietary Salt In Animal Modelsmentioning
confidence: 99%
“…10 In rodent studies, even the salt content contained in control diets (typically between 0.3 and 0.5%) may be well above biological needs, given evidence that rats ingest only 15% of this amount when allowed to freely consume a 0.5% NaCl solution alongside a salt-free solid diet and water. 38 A second consideration is that in some rodent studies, high-salt diets have produced cognitive impairments without altering blood pressure, 26,27,30 whereas others have shown cognitive deficits alongside hypertension 28,29 (Ta- Figure 1. Overview of evidence for adverse effects of salt intake on cognition and other health outcomes.…”
Section: Caveats and Considerationsmentioning
confidence: 99%
“…Surprisingly though, few studies have examined how elevated salt intake in rodents influences subsequent behavioral responses to stressors, particularly social interactions. Instead, most studies to date have either focused on the impact of high salt intake on memory (Chugh et al, 2013;Ge et al, 2017), or the influence of high salt consumption plus social stress on blood pressure (Adams and Blizard, 1986). Recently, we have observed that elevated salt intake heightened active coping responses of mice to swim stress, and recruited a pro-inflammatory cytokine with associated activation of microglia and neurons in stress-responsive brain nuclei (Mitchell et al, 2018;Gilman et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%